Bank Credit to Small and Medium-Sized Enterprises: The Role of Creditor Protection - Arturo Galindo; Alejandro Micco (Inter-American Development Bank, Research Department, 2005)
This paper develops a model showing that inefficient legal protections disproportionately increase financial restrictions for creditors that have less wealth. Due to fixed monitoring costs in equilibrium, banks will not monitor small firms, and therefore these firms will adopt risky technologies that imply a higher probability of bankruptcy. This implies that inefficiencies in the bankruptcy procedure will have a greater effect on small firms vis-à-vis large ones. Using a survey of firms in 62 countries around the world (WBES) and econometric techniques that allow us to deal with observed and unobserved country-specific components, as well as with partial endogeneity, the paper explore the role of creditor protection on small and medium-size enterprises access to bank credit. It is found that better protection of creditors reduces the financing gap between small and large firms.
Keywords: 330; KMU; Unternehmensfinanzierung; Kredit